Stachys lavandulifolia Causing Estrogen/Progesterone Imbalance during Pregnancy in Wistar Rat: A Time Course Experimental Study: Stachys Lavandulifolia induces abortion in rat - Ahmadimoghaddam, Davoud; Nili-Ahmadabadi, Amir; Shamahmudi, Amir Mohamad; Larki Harchegani, Amir; Moradkhani, Shirin (Iranian Journal of Pharmaceutical Sciences, 2021)
Stachys lavandulifolia is one of the most abortive herbs used in Iran. The present study aimed to investigate the effects of different doses of hydroalcoholic extract of Stachys lavandulifolia (HAESL) on serum estrogen and progesterone levels during different stages (implantation, abortion, and parturition) of pregnancy in Wistar rats. After observing vaginal plaque, the pregnant rats were randomly divided into three studied groups. Each group received the HAESL for three periods including, implantation (days 3 to 5), abortion (days 10 to 12), and parturition (days 19 to 21) of pregnancy. In the abortion and parturition periods, we observed a significant decrease in the estrogen level following administration of HAESL (300 and 900 mg/kg). In addition, we observed a significant decrease in the progesterone level at the highest dose of HAESL in all stages of pregnancy. In conclusion, the present study suggests that Stachys lavandulifolia may affect the estrogen/progesterone levels due to the presence of flavonoid compounds that subsequently lead to abortion, especially during the abortion and parturition periods.